Capacity-Development as Correlate of Access to Healthcare Services and Satisfaction among Health Care Workers and their Clients in Osun and Ogun States in Nigeria - Ekpo, Helen U.; Atulomah, Nnodimele O. (British Journal of Healthcare and Medical Research, 2024)
Nigeria is considered to have one of the lowest health indices in the world and contributes to 10 % of global maternal deaths. Households and individuals bear the burden of a dysfunctional and inequitable health system characterized by delayed or absence of seeking health care and having to pay out-of-pocket for health care services that are not affordable. Nigeria’s commitment to improvement of maternal and child health indices and Universal Health Coverage was symbolised by the passage of the National Health Act of 2014, section 11, which mandated the establishment of Basic Health Care Provision Fund (BHCPF) to expand the fiscal space by deploying financial resources for primary health care services [1]. Despite the introduction of the scheme, many states have not obliged to adopt the scheme. The study was Ex-post Facto cross-sectional design undertaken in Osun and Ogun States, to explore the relationship between capacity-development of health care workers in BHCPF supported facilities and quality of the services provided defined by satisfaction of services rendered and received by clients seeking health care and to demonstrate that these parameters are better in state that have adopted the BHCPF scheme for achieving UHC. Data collected were coded and analyzed using the Statistical Package for Social Sciences (SPSS) version 23, providing summaries which were used to derive test of significance of hypothesis. Clients in Osun State had significantly higher levels of satisfaction to the services received in BHCPF supported facilities when compared to those of clients accessing services in PHCs in Ogun state where the BHCPF had not commenced. The study findings provided some evidence to show that there is need for states governments in Nigeria to buy into the BHCPF program which is a veritable scheme that will contribute to provision of equitable health care services to all Nigerians and will contribute ultimately to achievement to universal health coverage to all Nigerians in the nearest future.